Inovasi Pembelajaran Ketauhidan Melalui Cerita Qur’ani Untuk Anak Usia Dini - Nihwan, Nihwan (Prodi PIAUD STAI Sumatera Medan, 2024)
This study aims to analyze the implementation, impact, and innovation of tawhid (monotheism) learning through the Qur’anic storytelling method at RA Al-Habib. Using a qualitative phenomenological approach, this research explores the experiences of teachers, students, and parents in understanding the values of tawhid through Qur’anic stories. The results show that the implementation of the Qur’anic storytelling method transforms the learning paradigm from a cognitive-transmissive approach into a narrative one that is emotional, contextual, and spiritual. Children not only comprehend the concept of the Oneness of Allah cognitively but also internalize tawhid values in their daily behavior through reflective activities and concrete experiences. Teachers utilize interactive media such as puppets, illustrations, and symbolic play to bring the stories to life, making learning more engaging and meaningful. The impact of this learning approach is reflected in the children’s enhanced spiritual awareness, active participation, and strong emotional engagement with tawhid values. This research offers an innovative, integrative, and applicable tawhid learning model based on Qur’anic stories, which is relevant to the development of Islamic education curricula for early childhood. Theoretically, this study strengthens the concept of narrative-based spiritual pedagogy, while practically it contributes to the design of humanistic, inspiring, and contextual learning models in RA institutions.